GENERAL PROBLEMS OF THE INTERDEPENDENT DEVELOPMENT OF THE BIOSPHERE AND URBANIZED ENVIRONMENT - Pozdnyakov, Andrey Leonidovich; Zvjagintseva, Marina Mikhaelovna (Journal of Applied Engineering Science, 2017)
Urbanization is a complex process, the understanding of which is treated differently by different specialties. If for the sociologist the main relations in this process are urban relations, even if they are taken in the whole breadth of their social content, then for the ecologist the manifestations of the biological consequences of urbanization are more important – the city’s attack on the living nature, the entire amount of negative impacts of urbanization on the ecosystems of the Earth. Urban formations act as extremely powerful centers of perturbation and degradation of the biosphere.
Keywords: Urbanization; Biosphere; Ecology; Nature management; Urban planning; Territorial dispersion